2010
DOI: 10.1007/s00198-010-1461-5
|View full text |Cite
|
Sign up to set email alerts
|

Spine–hip discordance and fracture risk assessment: a physician-friendly FRAX enhancement

Abstract: A simple procedure that incorporates the offset between the LS and FN T-scores can enhance fracture risk prediction under the FRAX system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
58
2
4

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 137 publications
(67 citation statements)
references
References 29 publications
3
58
2
4
Order By: Relevance
“…Fracture outcomes were available over a 10-year time frame. There was an approximately 10% change in fracture risk for each unit of T-score discordance [85].…”
Section: Assessment Of Bmd At the Lumbar Spine And Elsewherementioning
confidence: 99%
“…Fracture outcomes were available over a 10-year time frame. There was an approximately 10% change in fracture risk for each unit of T-score discordance [85].…”
Section: Assessment Of Bmd At the Lumbar Spine And Elsewherementioning
confidence: 99%
“…The impact of spine/femoral neck T-score discordance has recently been explored in a large BMD-referral population from Manitoba, Canada categorised according to Canadian guidelines [14,22] (Table 4). Fracture outcomes were available over a 10-year time frame.…”
Section: Limitations and Abuse Of Roc Analysesmentioning
confidence: 99%
“…The IOF-ISCD positions specifically state that measurements other than BMD or T-score at the femoral neck obtained by DXA should not be used with FRAX. The IOF-ISCD Task Force also concluded that FRAX may underestimate or overestimate major osteoporotic fracture risk when lumbar spine T-score is much lower or higher (>1 SD discrepancy) than femoral neck T-score, and that the offset adjustment described earlier (based upon the difference between the lumbar spine and femoral neck Tscores) could be used to enhance fracture prediction in the current version of FRAX [20]. The current study found that the weighted mean T-score input to FRAX was equivalent to the offset adjustment.…”
Section: Discussionmentioning
confidence: 99%
“…The tool, termed the Canadian Association of Radiologists and Osteoporosis Canada (CAROC) tool, calculates an initial risk category (low, <10%; moderate, 10-20%; high, >20% major osteoporotic fracture probability) based upon sex, age, and femoral neck T-score [17]. The offset adjustment used in the present analysis requires a continuous measure of fracture risk, and therefore, it cannot be used with CAROC [20]. However, the weighted mean T-score approach would be expected to provide an equivalent mechanism for incorporating the lumbar spine T-score into the fracture risk assessment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation